Testing the Popular Belief that Men Have Commitment Issues - Lange, Rense; Jerabek, Ilona; Dagnall, Neil (Journal of Scientific Exploration, 2023)
A sample of 36,592 online daters provided data on Commitment Readiness defined as “an individual’s desire and readiness to commit exclusively to one romantic partner” in relation to Age, Gender, and Parental Status (singles with and without children). Consistent with previous research, the women scored higher on Commitment Readiness than did the men. Furthermore, age and Commitment Readiness showed a strong inverted U-shaped relation, with younger and older respondents scoring lower on Commitment Readiness as compared to individuals aged 31-60 yrs. Interestingly, Commitment Readiness evidenced neither a significant effect of Parental Status nor an interaction of Gender by Parental Status. Besides the theoretical import of these results, our study illustrates the potential power of Internet research and provides a curious counterexample to criticisms of over-reliance on significance levels for correlational data.